HOCl vs OCl−: clarification on chlorine-based disinfectants used within clinical settings - Felicity V Mehendale; Gillian Clayton; Kate M Homyer; Darren M Reynolds (Journal of Global Health Reports)
Disinfection is a mainstay of infection prevention, the importance of which was highlighted throughout the SARS-CoV-2 pandemic. There is frequent misuse of terminology surrounding chlorine solutions in the literature. This leads not only to confusion but has potentially dangerous outcomes, as inappropriate mixing of chlorine solutions with other disinfectants or cleaning solutions can lead to the release of chlorine gas. This article provides a resource for accurate terminology surrounding chlorine-based disinfection and clarifies some of the key inaccuracies, including the pH-dependent nature of chlorine species distribution of hypochlorous acid (HOCl) (neutral/acidic chlorine solution) and hypochlorite (OCl-) (alkaline chlorine solution). Misuse and misunderstanding of chlorine solutions and the terminology used can be harmful therefore this is an essential resource for those utilising chlorine as a disinfectant.